Gunning for change: A content analysis of tweets following three mass shootings in the United States. - Damiano, Amanda D.; Xie, W.; Jong, C-H. (Atlantic Journal of Communication)
This study examined public comments on Twitter in the wake of three mass shootings in the United States during the summer of 2022. A total of 1,500 tweets were assessed (N = 1,500) for sentiment, risks presented, attribution of blame, and outrage. A sample of 500 tweets was taken following the Buffalo, New York, supermarket shooting; a sample of 500 tweets was taken following the Uvalde, Texas, school shooting; and a sample of 500 tweets was taken following the Highland Park, Illinois, Fourth of July parade shooting. Results show that risk, blame, and outrage differed significantly between the three situations in a variety of ways. These differences and possible reasons for them are further discussed. This study provides valuable insight on social media conversations about mass shootings – a timely subject that continues to plague the country and lead to polarizing opinions and divisiveness. The study also serves a practical function, as the findings can be presented to government organizations and social media organizations alike as critical insight into public perceptions, it can assist in identifying problematic speech online, and it can inform the development of social media guidelines in maintaining civil discord.